MITU-MACI Competitions. Participation in competitions in the context of continuous creative training of architects - Bulgakova, Elena (project baikal, 2017)
The article reviews the competition activity of the Department of Architecture in the context of various review competitions, festivals and conferences. The competition practices are analyzed considering the results of the Department’s creative activity, which is aimed at intensification of the educational process.